Development of Portable Water Quality Sampling Device for Water Dispenser Services - Muhammad Syahmir Hateem Sofian,; Nor Shahida Mohd Shah,; Amirul Syafiq Sadun, (Progress in Engineering Application and Technology, 2026)
Clean water from water dispenser is important for human to ensure it safe to drink. This project present the development of a portable water quality sampling device for water dispenser services to address the lack of real-time water quality monitoring. Traditional laboratory based testing method are time-consuming and unsuitable for continuous monitoring. The main objective of this project is to develop a portable device that can read the foreign object in clear water with other related reading while integrating Internet of Things (IoT) for data management and analysis. The system was developed using an ESP8266-based NodeMCU connected with multiple sensors and programmed using Arduino IDE, with real-time data transmission enabled through Wi-Fi to the Blynk and ThingSpeak platforms for monitoring and visualization. The evaluation was conducted by testing multiple samples from different water dispensers and the measured results were compared with standard laboratory reference values. The results indicate that the developed device is capable of providing stable, real-time water quality readings with acceptable accuracy and minimal deviation from reference standards. This innovative solution offers a cost-effective and reliable solution for real-time monitoring of water dispensers, and future work may focus on improving sensor calibration, expanding detection parameters, and enhancing system robustness for large-scale deployment.